The Influence of HR Management Quality on Improving the Performance of Contracting Companies in North Sumatra - Moses Hasiholan Septian Tampubolon; Gina Cynthia Raphita Hasibuan; M. Ridwan Anas; Ricky Bakara (Publikasi Indonesia, 2024)
This research aims to determine the influence of the quality of human resource management on the performance of contractor companies in North Sumatra. The hypothesis proposed is that there is a positive relationship between the quality of human resources and the performance of contractor companies. A total of 24 respondents from 6 contractor companies were selected as samples using the probability sampling method. The research results show that there is an influence between the quality of human resources on company performance. This is proven by the results of the hypothesis test which shows the calculated t value of 10.785, exceeding the t table value of 2.074. Therefore, the null hypothesis is rejected, indicating that there is a significant influence between the quality of human resource management and the performance of contractor companies in North Sumatra. From the research results, it can be concluded that the quality of human resource management has a significant influence on the performance of contractor companies in North Sumatra 84.1%; the remaining 15.9% is influenced by other factors. Therefore, it is recommended to improve the quality of human resource management to improve the performance of contractor companies.